A moda entre a arte e o design: do gesto aos processos de projetação - Taraciuk, Yuri Rezende (Universidade do Vale do Rio dos Sinos, 2022)
This research examines the place of Fashion between the fields of art and design, to propose an original design practice based on the relationships between these three areas. Through a critical analysis of the Fashion system and the place of its discourse in contemporary society, intrinsically linked to the hegemonic socio economic logic, we developed a creative method that takes its inspiration in the Dada movement and, in particular, the work of Marcel Duchamp. Under the influence of Dada, strategic design tools were reinterpreted for the execution of this project, materialized in the form of a fashion collection, but which focuses on the design process itself, or, as we also call it, the gesture. Understood as a practice that exceeds the verbal and the writing language, the gesture is the productivity before the constituted sign, which helps us to contemplate a displacement from the product for the production of meaning, realized by the designer, presented here both as the one who projects, as well as the one who reads the message. In this way, the design process developed in this work seeks to oppose traditional fashion design methods, placing chance and absurdity as a means to break with such models and, consequently, with the social values they convey.
Keywords: Sistema da moda; Arte; Design; Dadaísmo; Gesto; Fashion system; Art; Design; Dada; Gesture